IMPLEMENTASİ MODEL PHENOMENA BASED-INTERACTİVE CONCEPTUAL INSTRUCTİON (PB-ICI) DALAM PEMBELAJARAN IPBA UNTUK MENİNGKATKAN PENALARAN ILMİAH - Johan, Henny; Mayub, Afrizal; Wikrama Whardana, Rendy; umaya, Umaya; wati, Devica (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
Physics is a science that involves high curiosity about natural phenomena which are then solved using scientific methods. The learning program is designed to improve scientific reasoning skills, one of which is by using the Phenomena Based-Interactive Conceptual Instruction (PB-ICI) learning model. This research aims to implement the Phenomena Based-Interactive Conceptual Instruction (PB-ICI) learning model to improve students' scientific reasoning through IPBA courses. This research uses quasi-experiment, including pre-experimental, experimental and experimental data analysis stages. Based on the results of data analysis, it is known that student reasoning is spread across the categories of inductive-deductive reasoning at 30%), reasoning with evidence at 33%, reasoning with data at 33%, no reasoning at 3%, and undefined at 0%. The effectiveness of IPBA learning in instilling scientific reasoning is in the medium category with a distribution percentage of 63%. Based on these results, it can be interpreted that students have been able to organize various knowledge in the form of concepts, theories, laws, principles as well as data and facts to explain earth and space phenomena comprehensively. It can be concluded that IPBA learning using the PB-ICI model can train reasoning skills. After learning activities, 63% of the total students had reasoning in the categories of inductive-deductive reasoning and reasoning with evidence.